Dusty sheaths in non-equilibrium plasmas - Chutov, Yu.I.; Kravchenko, O.Yu. (Вопросы атомной науки и техники, 2003)
Self-consistent dusty sheaths are investigated using the kinetic PIC/MCC simulation of a temporal evolution of both dusty plasmas consisting of immersed electrodes (walls) and developing dusty discharges without special boundary conditions for the sheaths. Obtained results show an essential influence of dust particles on sheath parameters. Spatial distributions of a dust particle charge are not trivial due to a self-consistent evolution of electron and ion energy distribution functions.